DAMPAK LOKALISASI PROSTITUSI TERHADAP POLA HUBUNGAN KELUARGA DALAM PERSPEKTIF HUKUM ISLAM DI KAMPUNG KAJANG SINGA GEWEH SANGATTA SELATAN KUTAI TIMUR - Ghofur, Abd. (At-Tawazun, Jurnal Ekonomi Syariah, 2022)
The background of this research is to maintain family harmony in the localization of prostitution, both positive law and Islamic law in Indonesia. Based on this, the formulation of the problem raised by the author is How impact of prostitution localization on family relationship patterns in islamic law perspective in kampung kajang Singa Geweh South Sangatta District. There is also this research is a type of qualitative research with the research approach used is sociological juridical where this research is carried out to obtain legal knowledge empirically by going directly to the field. Data collection techniques in the form of observation, interviews, and documentation. The technique of taking respondents by means of a snowball is a method of taking samples in a chain and random manner.